Reciprocity in dynamic employment relationships - Matthias Fahn (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper explores how a relational contract establishes a norm of reciprocity and how such a norm shapes the provision of informal incentives. Developing a model of a long-term employment relationship, I show that generous upfront wages that activate the norm of reciprocity are more important when an employee is close to retirement. In earlier stages, direct incentives promising a bonus in exchange for effort are more effective. Then, a longer remaining time horizon increases the employer's commitment. Generally, direct and reciprocity-based incentives reinforce each other and should thus optimally be used in combination. I also show that more competition can magnify the use of reciprocity-based incentives. Moreover, with asymmetric information on the employee's responsiveness to the norm of reciprocity, an early separation of types is generally optimal. Then, the principal might benefit from asymmetric information because a firing threat is only credible if the employee potentially is not reciprocal.
Keywords: C73; D21; D22; D86; D90; D91; 330; reciprocity; relational contracts; dynamic incentives